IDENTIFIKASI CASH RATIO RUMAH SAKIT ISLAM SURABAYA - Agung Hendro Yuwono (UNUSA Press, 2018)
Cash ratio is an indicator for measuring the ability of company to pay short-term liabilities by available cash. Cash performance ratio in Islamic Hospital Surabaya only reached 61%, it indicates that Islamic Hospital Surabaya lack of working capital in cash for operations. This study aimed to evaluate policy account receivables cycle through policy evaluation approach. This study was an observational descriptive study using cross sectional design during six months. Data collection through analysis of secondary data, interviews and focus group discussion. Sources of information include hospital management and several departement such as service, marketing or public relations, and finance. Increasing of ability by liquidity, profitability and avtivity ratio in 2011 to 2015. Hospital management need to improve commitment building and determine reward, punishment for implementation in every policies and to arrange planning for policy evaluation that it has implemented.